Pengaruh Pelatihan dan Hypnomotivation terhadap Kinerja Karyawan - Maulana, Akhmad Adam; Yunida, Riswan; Amelia, Rini (P3M Politeknik Negeri Banjarmasin, 2025)
In the midst of rapid changes in the business environment, employee training has been recognized as an effective strategy to improve individuals’ skills, knowledge, and abilities in adapting to increasingly complex job demands. Meanwhile, high motivation is also an essential factor in determining employee performance. Deep and sustained motivation, known as hypnomotivation, has been proven to contribute to individual productivity and creativity. The objectives of this study are: (1) To determine whether training and hypnomotivation have a significant simultaneous effect on employee performance among AS Academy training participants; (2) To determine whether training has a significant partial effect on employee performance among AS Academy training participants; and (3) To determine whether hypnomotivation has a significant partial effect on employee performance among AS Academy training participants. This study employed a quantitative descriptive statistical method, with data collected through questionnaires distributed via Google Forms to 109 participants and analyzed using IBM SPSS. The results show that: (1) Training and hypnomotivation have a significant simultaneous effect on employee performance among AS Academy training participants; (2) Training has a significant partial effect on employee performance; and (3) Hypnomotivation has a significant partial effect on the performance of AS Academy training participants.